Preliminary landscape of Candidatus Saccharibacteria in the human microbiome - Naud, Sabrina; Valles, Camille; Abdillah, Abdourahim; Abou Chacra, Linda; Mekhalif, Fatima Zouina; Ibrahim, Ahmad; Caputo, Aurelia; Baudoin, Jean-Pierre; Gouriet, Frédérique; Bittar, Fadi; Lagier, Jean-Christophe; Ranque, Stéphane; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Candidate Phyla Radiation (CPR) and more specifically Candidatus Saccharibacteria (TM7) have now been established as ubiquitous members of the human oral microbiota. Additionally, CPR have been reported in the gastrointestinal and urogenital tracts. However, the exploration of new human niches has been limited to date. In this study, we performed a prospective and retrospective screening of TM7 in human samples using standard PCR, real-time PCR, scanning electron microscopy (SEM) and shotgun metagenomics. Using Real-time PCR and standard PCR, oral samples presented the highest TM7 prevalence followed by fecal samples, breast milk samples, vaginal samples and urine samples. Surprisingly, TM7 were also detected in infectious samples, namely cardiac valves and blood cultures at a low prevalence (under 3%). Moreover, we observed CPR-like structures using SEM in all sample types except cardiac valves. The reconstruction of TM7 genomes in oral and fecal samples from shotgun metagenomics reads further confirmed their high prevalence in some samples. This study confirmed, through their detection in multiple human samples, that TM7 are human commensals that can also be found in clinical settings. Their detection in clinical samples warrants further studies to explore their role in a pathological setting.